Occurrence of microplastics in the mangrove sediments and "balihasa" clams (Gafrarium pectinatum) of Tabuelan, Cebu - Elmido, Catherine P.; Silapan, Judith R. (Cebu City, Cebu Department of Biology and Environmental Science, College of Science, University of the Philippines Cebu, 2022)
Mangroves are considered microplastic (MP) sinks due to their unique characteristics (dense vegetation, roots, and steady water currents) that potentially trap small plastic pollutants. With either chemical or mechanical degradation of macroplastics, the resulting MPs can get deposited into the sediments making them highly available to sediment-dwelling and filter-feeding biota such as bivalves. The primary objective of this study was to assess MP occurrence in the sediment and ?balihasa? clams (G. pectinatum) of three selected mangrove sites (Sitio Can-ambay, Cansimon, and Magsaysay) of Tabuelan, Cebu. At each sampling site (n=3), three sediment samples and thirty clam individuals were collected using random and convenience sampling, respectively. Both sediment and clam samples were subjected to a series of digestion, flotation, and filtration methods to isolate MPs. Analysis of MPs was done under a compound microscope, verifying their identities using the hot needle method. Results showed that MPs were present in both mangrove sediments and ?balihasa? clams of Tabuelan, Cebu, but in low concentrations. MP abundance in mangrove sediments ranged from 12.3 ± 1.5 to 19.7 ± 3.1 items kg-1 while in clams, mean MP loads ranged only between 0.26 to 0.51 items g-1. MP loads of the clams are independent of that of the MP abundance in the sediments, possibly due to the low sample size and patchy distribution of MPs per site. Fibers, MPs of size range <500 μm, and blue-colored MPs are dominant in all sample types across sampling sites, suggesting similar sources of plastic pollutants. The MPs in clams are also found to be independent of the MPs found in the sediments in terms of type, size, and color. Nevertheless, the similarities of MP characteristics in both sediment and clam samples suggest the MP availability in the environment and the possible ingestion of these by filter-feeding G. pectinatum.
Thesis (Bachelor of Science in Biology). University of the Philippines Cebu. June 2022.